Transformasi Kurikulum Bahasa Arab: Analisis Lima Pendekatan dalam Penguatan Kemahiran Berbahasa untuk Peradaban Islam Masa Depan - Adyllah, Nola; Marhamah Ulfa; Rizka Sari; Salahuddin Al Asadullah; Anwar Sidik; Sri Masyitah; Siti Kholifah (Institut Muslim Cendekia, 2025)
The transformation of the Arabic language curriculum is essential for developing language skills that meet the challenges of the contemporary era and the needs of the future Islamic civilization. This study aims to analyze the transformation of the Arabic curriculum through five curriculum evaluation approaches: goal-oriented, need assessment, formative, responsive, and connoisseurship. Using a qualitative literature study and descriptive analysis of curriculum documents and previous evaluation results, the research found that the current Arabic curriculum is still dominated by cognitive approaches such as memorization and grammar, while communicative skills and students’ contextual needs are less addressed. Formative assessments and stakeholder participation in curriculum development are also limited. The novelty of this study lies in its recommendation for an integrative curriculum transformation combining language competencies, Islamic values, cultural identity, and 21st-century skills. The implication is the urgent need to revise the curriculum to be more responsive to students’ needs and global challenges, thus producing future generations capable of active contributions to Islamic civilization.